Peces criptobentónicos de arrecifes coralinos en el Parque Nacional Archipiélago de Los Roques, Caribe de Venezuela - G. Rodríguez-Quintal, José (2010)
A sig-nificant portion of coral reef fish assemblages are composed of small cryptobenthic fishes, but these are poorly represented in regional fish characterization works. We characterized the cryptobenthic reef fishcommunity associated with coral reef in Los Roques National Park during six week surveys. The study included 11 locations in which these fish were registered in transects of 10x2m. Specimens were collected using the suction method and a fine-mesh net. A total of 31 species of six families were collected (four Blenniidae, six Chaenopsidae, one Gobiesocidae, 12 Gobiidae, seven Labrisomidae and one Tripterygiidae). Six represented new records to the park, and Coralliozetuscardonae (Chaenopsidae) was a new record for Venezuela. The most important families were Gobiidae, Chaenopsidae and Labrisomidae. Cryptic fish assemblages changed with the reef environments, with a clear distribution pattern: some species were only observed in shallow areas of less than 5m depth, while in fringing and barrier reef areas, other species were present and differentially distributed between the reef crest and the seaward slope. These patterns probably are related to the close association that these small fish maintain with the benthos.